Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Teams Assisted Individualization di Sekolah Dasar - Rahmi, Intan Aulia; Ahmad, Syafri (Universitas Negeri Padang, 2023)
This study was inspired by the implementation of student learning that lacks a feeling of obligation to the group, there has been no interaction and cooperation between group members, often only one or two people are actively working in groups. This investigation intends to clarify the enhancement of incorporated thematic instruction results utilizing the model of teamwork in education with team-assisted individualization in grade V SDN 18 South Air Tawar Padang City. a classroom action research project, this investigation project it took place during two cycles, using quantitative and qualitative, each of which cycles had ways for gathering data, including non-tests, testing, and observation Planning, carrying out, observing, and reflecting are the four stages. Teachers and grade V pupils, a total of 17, were the study's subjects. The findings indicated: a) Observation of RPP in cycle I 85, 93% buoyant to 96.87% in cycle 2, b) cycle of teacher activities implementation I 85, 93% buoyant to 93.75% in cycle II, putting into practice student activities in cycle I 85, 93% buoyant to 93.75% cycle II, c) Cycle of consequences for student learning I found that on average 79 buoyant to 90 in cycle II.